2012
DOI: 10.1143/apex.5.122102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nanosized Ni Particle Structure on the Enhancement of Light Extraction from 600 nm AlGaInP Light-Emitting Diodes

Abstract: This paper reports on the effect of Ni particle structures on the light extraction in 600 nm AlGaInP light-emitting diodes (LEDs). A Ni film was deposited on top of a gallium phosphide (GaP) layer and the surface texture was improved by an ammonia (NH 3 ) plasma etching process into a chamber resulting in the formation of Ni particles with an average size of 10 nm. AlGaInP LED with the Ni particle shows an increase in the light extraction by 75% and a higher emission intensity with a percentage increase of 112… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The output power for NIR-LEDs can be increased by using multiple quantum wells (MQWs), window layers, distributed Bragg reflectors (DBRs), omnidirectional reflectors (ODRs), and current-spreading layers. MQWs are used to maximize the internal quantum efficiency of the active region in NIR-LEDs [ 5 ]. To improve the optical efficiency of NIR-LEDs with an absorbing substrate, a DBR must be used because it reflects the photons emitted from the active area in an upward direction [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The output power for NIR-LEDs can be increased by using multiple quantum wells (MQWs), window layers, distributed Bragg reflectors (DBRs), omnidirectional reflectors (ODRs), and current-spreading layers. MQWs are used to maximize the internal quantum efficiency of the active region in NIR-LEDs [ 5 ]. To improve the optical efficiency of NIR-LEDs with an absorbing substrate, a DBR must be used because it reflects the photons emitted from the active area in an upward direction [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extant studies have already indicated the relationship between light extraction efficiency and a few factors (such as textured structure and relative intermediate refractive index) significantly influence the output power of the light emitter. [16][17] Based on the hypothesis and experiment, the output power of the VCSEL was significantly increased by using the textured structure formed on both the top DBR and the anti-reflection film. Furthermore, the results verified that the obtained output power was further increased due to the relative intermediate refractive index of the anti-reflection film.…”
Section: Introductionmentioning
confidence: 96%
“…To meet the demands of these applications, small NIR-LEDs that can deliver higher power outputs at large injection currents are required. For several years, multiple quantum wells (MQWs), distributed Bragg reflector (DBR), omni-directional reflector (ODR), and current spreading layers have been used to improve the output powers in NIR-LEDs [ 3 , 4 , 5 , 6 ]. However, the abrupt decrease in the surface-emitting area of these devices, due to a reduction in the chip size, was not investigated in prior research efforts [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%